CULTURAL RECOGNITION APPLICATIONS WEBSITE SPECIALLY NUSANTARA CLOTHES FOR STUDENTS AND HOUSE PRIMARY ADAT USING MACROMEDIA DREAMWEAVER 8 - Nurlina Nofiyanti; Hariyanto., SKom., MMSi Hariyanto., SKom., MMSi (Jurnal Sistem Informasi, 2007)
Internet is now become a choice of the most effective in disseminating information,because the Internet has a network coveragewide. One of the great information that gets a place on the Internet, among others,information relating to education. This information is conveyed through one of thestorage media is information on the Internet Website.Scientific writing is trying to explain how making a website about culturalrecognition of the archipelago, especially clothing and custom house for elementaryschool students. Starting from design stage design, making websites ready to publishon the Internet. All were created using Macromedia Dreamweaver 8.